DIMENSI LIBERASI DALAM NOVEL BUMI CINTA KARYA HABIBURRAHMAN EL SHIRAZY: DIMENSIONS OF LIBERATION IN THE NOVEL EARTH OF LOVE BY HABIBURRAHMAN EL SHIRAZY - Fatmawati, Fatmawati; Hoar , Bonifasia; Akbar , Ari Rizky; Fatin, Yustina Mince (IKIP Siliwangi, 2025)
The dimension of liberation contained in a literary work can be a solution to control social problems. Through these liberatory values, humans are taught to free themselves from life practices that are shackling. This study aims to describe the dimension of liberation contained in the novel Bumi Cinta by Habiburrahman El Shirazy. This study uses a qualitative method with a content analysis approach. The data source in this study is the novel Bumi Cinta, while the data are in the form of quotations containing the dimension of liberation. The results of this study found 5 data points that describe liberation from ignorance, and 3 data points that describe liberation from oppression. The dimension of liberation that appears in this novel is related to the knowledge and social systems. This dimension of liberation reflects resistance against intellectual backwardness and practices of oppression in life.